2016
DOI: 10.1093/jnen/nlw092
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Traumatic Encephalopathy-Like Abnormalities in a Routine Neuropathology Service

Abstract: Chronic traumatic encephalopathy (CTE) has been described mainly in professional athletes and military personnel and is characterized by deposition of hyperphosphorylated tau at the depths of cortical sulci and around blood vessels. To assess CTE-like changes in a routine neuropathology service, we prospectively examined 111 brains (age 18-60 years). The presence of tau-immunoreactive deposits was staged using guidelines described by others and was correlated with the medical history. 72/111 cases were negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…Continuous tau deposition in the cortical lamina differentiated AD from CTE, as does the absence, in CTE, of NFT deposition in other parts of the cortex and limbic system, particularly in milder cases of CTE. However, data show that up to 37% of individuals diagnosed with CTE pathology also met criteria for comorbid neurodegenerative pathology including AD, Lewy Body Disease, and frontotemporal lobar degeneration 5 , largely in older subjects, CTE has been identified almost exclusively in individuals with a history of repetitive brain trauma, though some recent findings raise questions of whether such exposure is necessary 32,33 . Lack of prospective longitudinal studies or validated in vivo diagnostic markers, and current sample biases significantly limit accurate determination of CTE incidence and prevalence.…”
Section: Repetitive Brain Trauma and Neurodegenerationmentioning
confidence: 99%
“…Continuous tau deposition in the cortical lamina differentiated AD from CTE, as does the absence, in CTE, of NFT deposition in other parts of the cortex and limbic system, particularly in milder cases of CTE. However, data show that up to 37% of individuals diagnosed with CTE pathology also met criteria for comorbid neurodegenerative pathology including AD, Lewy Body Disease, and frontotemporal lobar degeneration 5 , largely in older subjects, CTE has been identified almost exclusively in individuals with a history of repetitive brain trauma, though some recent findings raise questions of whether such exposure is necessary 32,33 . Lack of prospective longitudinal studies or validated in vivo diagnostic markers, and current sample biases significantly limit accurate determination of CTE incidence and prevalence.…”
Section: Repetitive Brain Trauma and Neurodegenerationmentioning
confidence: 99%
“…3 We have an incomplete understanding of the extent or distribution of pathology required to produce neurological dysfunction or to distinguish diseased from healthy tissue, with the neuropathological changes of CTE reported in apparently asymptomatic individuals. 4,5 Although commonly quoted, no consensus agreement has been reached on staging the severity of CTE pathology. A single focus of the pathology implicated in CTE is not yet sufficient evidence to define disease.…”
mentioning
confidence: 99%
“…The long-term effect of repetitive concussion of boxers and other athletes showed a unique pattern of pathology first described in 1973 by Corsellis et al [11] It is characterized by irregularly distributed NFTs and NTs with phosphorylated and 4R tau protein accumulation especially in the depth of cerebral sulci and perivascular area [1359]. Ghajari et al reported the computerized modelling images of CTE [12].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic traumatic encephalopathy (CTE) is a progressive degenerative disease and progressive tauopathy of the brain caused by sequelae of head trauma and is common in athletes or patients with recurrent brain trauma such as boxers, professional soccer players, professional wrestlers, epilepsy patients, head bangers and domestic violence victims [123456]. The name CTE was created in 1949 by Critchley.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation